Functional Gradient Metallic Biomaterials: Techniques, Current Scenery, and Future Prospects in the Biomedical Field - Shi, Hongyuan; Zhou, Peng; Li, Jie; Liu, Chaozong; Wang, Liqiang (Frontiers in Bioengineering and Biotechnology, 2021)
Functional gradient materials (FGMs), as a modern group of materials, can provide multiple functions and are able to well-mimic the hierarchical and gradient structure of natural systems. Because biomedical implants usually substitute the bone tissues and bone is an organic natural FGM material, it seems quite reasonable to use the FGM concept in these applications. These FGMs have numerous advantages, including the ability to tailor the desired mechanical and biological response by producing various gradations like compositional, porosity, size, mitigating some limitations like stress-shielding effects, improving osseointegration, enhancing electrochemical behavior, and wear resistance. Although these beneficial aspects, there is still a big lack of comprehensive guidelines and standards. This paper aims to comprehensively review the current scenery of FGM metallic materials in the biomedical field, specifically its dental and orthopedic applications. It also introduces various processing methods, especially additive manufacturing methods that have a substantial impact on FGM production, mentioning its prospect and how the FGMs can change the direction of both industry and biomedicine. Any improvement in FGM knowledge and technology can lead to big steps toward its industrialization and most eminently for much better implant designs with more biocompatibility and similarity to natural tissues that finally enhance the life quality of human beings.